The Role Of School Counselors To Helping Student in Puberty Through The Collaborative Paradigm - Ramdani Ramdani; Tamama Rofiqah; Imalatul Khairat; Muhammad Putra Dinata Saragi; Randi Saputra (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2020)
Adolescent is one of the stages in human life that is very critical, because it is a stage of transition from childhood to adulthood. At this stage a lot of changes occur in adolescents, such as physical, emotional and social changes. This period of change is commonly referred to as the period of puberty. The puberty period is also considered an overlapping period because it covers the final years of the childhood period and the early years of the teenage period. Changes experienced by adolescents in the puberty period are often troubling because the various changes that occur are considered as a very disturbing clumsiness. As good puberty teenagers, they are expected to understand the physical, emotional and social changes they experience. School counselors have a large role in helping students deal with periods of puberty. This role is reflected in the counseling guidance service provided to help students deal with the period of puberty so that giving birth to a good assessment of the puberty teenager on the changes they experience and puberty teenagers will have a positive self-concept in their lives. Guidance and counseling services provided by school counselors in helping students deal with periods of puberty cannot be done alone. Requires cooperation in the collaborative paradigm in implementing it. The implementation of guidance and counseling services with the collaboration paradigm enables counselors to use other resources to support the implementation of services